SMART CAMPUS FRAMEWORK: DEFINITION, MODEL, MEASUREMENT FROM ANTHROPOCENTRIC, SYSTEMIC AND TECHNOLOGICAL SMARTNESS PERSPECTIVES - Victor Imbar, Radiant
The world is entering the era of Industrial Revolution 4.0 which is moving the world towards a new technology-based ecosystem so that the term "smart system" is widely used in various fields. The field of Information Technology is a field that uses smart systems, both for smart building systems, smart city systems, even smart campus systems. The current challenge for Higher Education (HEI) is to increase efficiency in completing education and be able to increase competitiveness against competitors and become an attraction for prospective students so they can survive amidst disruption and high competition. The way to do this is by implementing a smart system within the HEI which is known as a smart campus. Smart campus is a holistic solution, so it is not easy to implement or adopt a smart system according to campus needs, so a framework is needed to simplify and increase the potential for success in implementing a smart system. In this research, a smart campus framework was designed which could be a solution for HEIs in developing smart campuses and measuring smart campuses. The Design Science Research Methodology (DSRM) methodology is used in developing the smart campus framework. The smart campus framework consists of a smart campus definition which is used as a reference for this research in creating a smart campus model and a smart campus measurement model. The smart campus model is created as an ideal model if a campus wants to transform into a smart campus because it contains smart system-based services that a smart campus must have, and a smart campus measurement model is created to measure the smart system-based services provided by a smart campus. The smart campus framework was evaluated in the HEI environment in Indonesia to measure the current condition of campus smartness. With this evaluation environment, the current smartness condition of the campus can be known, thereby creating various potential innovations that can be carried out by a campus towards a smarter campus and as a means for testing the framework that has been created. The smart campus framework was also evaluated qualitatively using expert judgment.